Basic Multicultural Concepts: The Nature, History and Ideas of Gender Equality - Selamat Ariga; Anisa Hayati Rahman; Hafizur Rohim Nasution; Muhammad Iqbal Ardian Toni Siahaan (Yayasan Zia Salsabila, 2023)
The plurality of society is a unique wealth of the Indonesian nation. To maintain harmony between communities, multicultural-based humanist teaching is needed. This research was conducted with the aim of revealing the basic concept of multiculturalism from the aspects of understanding, history, goals, and principles that exist in multicultural education. The method used in this research is library research or library study, which is an activity related to library data collection methods, both by reading and taking notes as well as processing research materials using various sources such as books, journals, thesis results, and so on discussion material. The results of this research show that the history, goals, and principles of multicultural education have an important role in dealing with diversity. Through multicultural education, humanist, tolerant, and democratic attitudes can be instilled.